Dialogue, Discernment, and Creative Tensions in Jesuit Higher Education - Trinidad, Jose Eos R (Archīum Ateneo, 2021)
Like most higher education institutions, Catholic universities experience changes and pressures due to university rankings, education marketisation, and diverse student bodies. As part of the Catholic Church, these institutions must also be faithful to their unique religious identity and mission. In this paper focusing on Jesuit institutions, the concept of creative tension is explored as it operates in the student, faculty, and institutional levels. For students, Jesuit universities make efforts to balance both professional and holistic education; for faculty, the focus is on the balance of professional and institutional involvement; for institutions, the balance of teaching and research, and service for justice and faith. The paper discusses how these tensions are present in Jesuit schools, and how its creativity is the product of dialogue and discernment.